2021
DOI: 10.1002/asia.202001271
|View full text |Cite
|
Sign up to set email alerts
|

Apparent Kinetics of Co‐Gasification of Biomass and Vacuum Gas Oil (VGO)

Abstract: This communication reports the beneficial effects of co‐gasification of biomass and residual oil to produce syngas. In this regard, various blends of glucose (a biomass surrogate) to vacuum gas oil (VGO) have been employed to investigate the synergic effects on the gasification process. The non‐isothermal co‐gasification experiments were conducted in a thermogravimetric analyzer at different heating rates and gasifying agents. The analysis showed that the co‐gasification rate increased with the increase of glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 67 publications
(101 reference statements)
0
1
0
Order By: Relevance
“…They observed that the gasification combined cycle efficiency is in the range of 49-50.7%. Al-Attas et al [25] have studied the co-gasification of biomass and vacuum residue to produce syngas. He discovered that with the addition of biomass, the oxygen contents of the gasification reactions are assisted as their activation energy becomes lowered.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that the gasification combined cycle efficiency is in the range of 49-50.7%. Al-Attas et al [25] have studied the co-gasification of biomass and vacuum residue to produce syngas. He discovered that with the addition of biomass, the oxygen contents of the gasification reactions are assisted as their activation energy becomes lowered.…”
Section: Introductionmentioning
confidence: 99%